2006
DOI: 10.1038/sj.jp.7211576
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable fortification of human milk fed to preterm infants

Abstract: In adults, as protein intake increases, so does blood urea nitrogen (BUN), unless significant protein accretion is occurring and/or hepatic function; that is urea synthetic capacity, is compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…Our study showed no significant differences in the postnatal growth of premature infants who received supplemental enteral protein when compared to the infants who received standard premature milk mixtures. The results of this study are not congruent with the findings of other recent research in which increased enteral protein intake significantly improved weight gains when compared to standard enteral protein intake [9,12,13,[21][22][23][24][25][26][27][28][29][30].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed no significant differences in the postnatal growth of premature infants who received supplemental enteral protein when compared to the infants who received standard premature milk mixtures. The results of this study are not congruent with the findings of other recent research in which increased enteral protein intake significantly improved weight gains when compared to standard enteral protein intake [9,12,13,[21][22][23][24][25][26][27][28][29][30].…”
Section: Discussioncontrasting
confidence: 99%
“…Both individualization methods have been shown to be superior to standard fortification in terms of both weight gain and increases in head circumference . Adjustable fortification is considered practical and simple; it does not require analyses of breast milk, and the BUN level is frequently used as a valuable parameter in routine clinical practice . On the other hand, BUN analysis may not completely reflect the protein intake of VLBW infants, particularly in the first weeks of life .…”
Section: Discussionmentioning
confidence: 99%
“…9 At an intake of 3.0 g per 100 kcal, protein assimilation (2.7 g kg À1 per day) somewhat exceeded that 'in utero' (2.5 g kg À1 per day) and was paralleled by normal growth (27 g per day) and serum chemistries. 8,15 A further examination of the biochemical differences is therefore warranted. Statistically significant but small differences were noted in BUN, total protein, albumin, calcium and phosphorus levels between the groups.…”
Section: Discussionmentioning
confidence: 99%